2021
DOI: 10.3390/app11136178
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Diagnosis of Diabetic Retinopathy and Glaucoma Using Retinal Fundus Images Based on Hybrid Features and Genetic Algorithm

Abstract: Diabetic retinopathy (DR) and glaucoma can both be incurable if they are not detected early enough. Therefore, ophthalmologists worldwide are striving to detect them by personally screening retinal fundus images. However, this procedure is not only tedious, subjective, and labor-intensive, but also error-prone. Worse yet, it may not even be attainable in some countries where ophthalmologists are in short supply. A practical solution to this complicated problem is a computer-aided diagnosis (CAD) system—the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The image annotation is done initially to remove noisy artifacts in DFI. A comprehensive review of semantic fundus image segmentation [4] was done to analyze the masking and segmentation processes in various pretrained network architectures. The author contributed the clinical dataset values in a single array system where all the fundus images are segmented in the model and compared with other datasets and clinical results.…”
Section: Related Workmentioning
confidence: 99%
“…The image annotation is done initially to remove noisy artifacts in DFI. A comprehensive review of semantic fundus image segmentation [4] was done to analyze the masking and segmentation processes in various pretrained network architectures. The author contributed the clinical dataset values in a single array system where all the fundus images are segmented in the model and compared with other datasets and clinical results.…”
Section: Related Workmentioning
confidence: 99%
“…Table 2 and Figure 10 offer an extensive comparative study of the AI‐ODCNN model on the ARIA dataset (Chea & Nam, 2021; Liu et al, 2019; Tamim et al, 2021). The results indicated that the ResNet‐152 model has shown ineffectual classification results.…”
Section: Performance Validationmentioning
confidence: 99%
“…Retinal diseases include Choroidal Neovascularization (CNV), Age-Related Macular Degeneration (AMD), Diabetic Macula Edema (DME), glaucoma, Drusen and diabetic retinopathy (DR) [3]. Tamim et al [4] predicted that the number of people with glaucoma will peak to 111.8 million people by 2040. According to Chelaramani et al in [5] in 2015, 415 million people were suffering from diabetes, of which 145 million had DR. Chelaramani et al [5] further stated that AMD affects 6.2 million people globally.…”
Section: Introductionmentioning
confidence: 99%